2023
DOI: 10.3390/land12050988
|View full text |Cite
|
Sign up to set email alerts
|

Challenges and Opportunities for Cover Crop Mediated Soil Water Use Efficiency Enhancements in Temperate Rain-Fed Cropping Systems: A Review

Abstract: Soils are at the nexus of the atmospheric, geological, and hydrologic cycles, providing invaluable ecosystem services associated with water provision. The immeasurably vital role of water provision is of urgent concern given the intertwined and interdependent challenges of growing human populations, increased agricultural demands, climate change, and freshwater scarcity. Adapting temperate rain-fed cropping systems to meet the challenges of the 21st century will require considerable advancements in our underst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 92 publications
(132 reference statements)
0
1
0
Order By: Relevance
“…An analysis of variance (ANOVA) was used to check whether there is a statistically significant variance reported in crop production and households' income between treated and non-treated plots. In relation to this, Moore (2023) indicated that analysis of variance (ANOVA) enables a comparison of variances between treatment and control units. Similarly, ANOVA was applied to ascertain the variation between the control and one or more treatment groups (Tadikamalla et al, 2003;Degfe et al, 2023).…”
Section: Methods Of Data Analysismentioning
confidence: 99%
“…An analysis of variance (ANOVA) was used to check whether there is a statistically significant variance reported in crop production and households' income between treated and non-treated plots. In relation to this, Moore (2023) indicated that analysis of variance (ANOVA) enables a comparison of variances between treatment and control units. Similarly, ANOVA was applied to ascertain the variation between the control and one or more treatment groups (Tadikamalla et al, 2003;Degfe et al, 2023).…”
Section: Methods Of Data Analysismentioning
confidence: 99%
“…When comparing the soil VWC in relation to soil temperature and percent cover, no distinct pattern was observed. The absence of a clear connection may stem from the intricate relationship between CCs and soil water content (Moore, 2023). Additionally, environmental factors such as location, soil, and climate conditions can influence the relationship between CCs and soil water content (Wang et al, 2021).…”
Section: Soil Vwcmentioning
confidence: 99%
“…Adding to the functional biodiversity of cropping systems has been shown to enhance productivity (Franco et al, 2015), yield stability (Khan and McVay, 2019;Franco et al, 2021b), and substantially increase soil health metrics (McDaniel et al, 2014;Costa et al, 2018;Sprunger et al, 2020). Articles in this Research Topic also highlight how functional biodiversity can increase crop pest suppression [Brockmueller et al; Bruce et al(b)], retain nutrients (Wepking et al), and augment soil water retention (Nichols et al, 2022;Moore, 2023).…”
Section: Functional Biodiversitymentioning
confidence: 99%